Morphological Change of a PbSe film grown by Chemical Bath Deposition during Sensitization. Issue 1804 (2015) - Suh, Youngjoon; Suh, Sang Hee
ABSTRACT: A PbSe film was grown by chemical bath deposition on a thermally oxidized Si (111) substrate. Morphological change of the PbSe film during sensitization under the oxygen and iodine atmospheres was studied by SEM. The as-grown polycrystalline PbSe film consists of clusters of about 200nm in diameter. By the oxidation treatment for 30 min at 380°C, the clusters became joined together. On the other hand, recrystallization of new PbSe crystals with faceted surfaces occurred during the iodination treatment under an iodine plus nitrogen atmosphere at 380°C for different durations. This morphological change during the sensitization treatment might affect the electro-optical properties of the PbSe film.